Microtissues in Cardiovascular Medicine: Regenerative Potential Based on a 3D Microenvironment - Julia Günter; Petra Wolint; Annina Bopp; Julia Steiger; Elena Cambria; Simon P. Hoerstrup; Maximilian Y. Emmert (Stem Cells International)
More people die annually from cardiovascular diseases than from any other cause. In particular, patients who suffer from myocardial infarction may be affected by ongoing adverse remodeling processes of the heart that may ultimately lead to heart failure. The introduction of stem and progenitor cell-based applications has raised substantial hope for reversing these processes and inducing cardiac regeneration. However, current stem cell therapies using single-cell suspensions have failed to demonstrate long-lasting efficacy due to the overall low retention rate after cell delivery to the myocardium. To overcome this obstacle, the concept of 3D cell culture techniques has been proposed to enhance therapeutic efficacy and cell engraftment based on the simulation of an in vivo-like microenvironment. Of great interest is the use of so-called microtissues or spheroids, which have evolved from their traditional role as in vitro models to their novel role as therapeutic agents. This review will provide an overview of the therapeutic potential of microtissues by addressing primarily cardiovascular regeneration. It will accentuate their advantages compared to other regenerative approaches and summarize the methods for generating clinically applicable microtissues. In addition, this review will illustrate the unique properties of the microenvironment within microtissues that makes them a promising next-generation therapeutic approach.